Reducing Learners’ Speaking Anxiety through the Use of Oral Presentation Projects in EFL Classes. The case of third year students at the Department of English at the University Amar Telidji -Laghouat - Barkat ,Fatima; Ghabani ,Kaouthar Nour El Yakine; KORICHI ,Souhila (Faculty of Letters and Foreign Languages Department of English, 2016)
This study aims at showing the effect of using oral presentation projects in reducing learners‟ speaking anxiety in EFL classes. The purpose of this study aims at identifying the main sources of this anxiety and showing how oral presentations projects are helpful in reducing it. Another aim is to collect data in an attempt to figure out the sources of the problem, then to provide suggestions to enhance students‟ self-confidence. In order to conduct this study, one instrument is used to collect data. A questionnaire was administered to third year students of English at Amar Telidji University. It is conducted to ask 30 students about their main sources of speaking anxiety and their views about using oral presentation projects as a helpful instrument in EFL classes. The results of the study reveal that the main sources of anxiety are: a lack of practice, the fear of negative feedback, learners‟ false beliefs about language learning, the fear of failing the English oral test and the worry about teachers‟ way of error correction. The findings also show that students are aware of the importance of using oral presentation projects in reducing their speaking anxiety in EFL classes as well as their future professional career. Students show that they lack practice because teachers only sometimes ask them to do such activity. Therefore, students are in need of more practice to reduce this anxiety and improve self-confidence